Types and archetypes in Motyl's variation on a medieval theme. - Hrtanek, Petr (Bohemica Olomucensia, 2023)
This article deals with the novel by Petr Motyl Pribeh pana rytire Vitka a jeho dcery Anezky (The Story of Knight Vitek and his daughter Anezka, 2020). It focuses on types of characters and archetypal motifs, using Northrop Frye's concept of mythoi, i. e. narrative plots (comedy, romance, tragedy, satire) connected with seasons and vegetation cycles. It is reflected in subgenre metamorphoses of Petr Motyl's historical fiction.
Keywords: Petr Motyl; historical fiction; types of characters; archetypal motifs; mythos